MEASUREMENT AND ASSESSMENT OF BULLYING BEHAVIOURS IN DEPARTMENTS AND AFFILIATED COLLEGES OF UNIVERSITY OF DELHI - Singh, Kavita (PEOPLE: International Journal of Social Sciences, 2017)
Workplace bullying has received tremendous attention both from the academicians and the researchers in last few years. Bullying predominantly results in unfavourable consequences both for the individual, who is a victim, and the organization which supports such deviant behaviour. The most common effects of bullying in organization have been lowered performance, decreased commitment, higher absenteeism and intention to leave the organization. The present study is envisaged to analyze the existence of bullying behaviours in the university departments and affiliates colleges of University of Delhi. It was found that most of the bullying came from the seniors and the boss in colleges with colleagues being the next major source. It was evident that excessive criticism by the seniors and bosses was the most prevalent bullying form followed by threats and constantly changing instructions. With respect to affect of bullying, depression and irritability were top on the list of symptoms followed by loss of confidence and self esteem, fear of going to work, headache and loss of sleep. Most of the bullied employees reported the matter either to their colleague or to their seniors in the college. Two-third of the respondents believed that the culture of bullying did not exist in the system while one-third believed that it was present. Research has begun to shed light on how the structure and context of academe can promote bullying and harassment behaviours, but much more needs to be done to understand how often these behaviours occur, why they occur, and the effective means to combat their prevalence on campus